Particle therapy in adult patients with pelvic ewing sarcoma: tumor and treatment characteristics and early clinical outcomes - Schmid, Maximilian P.; Harrabi, Semi B.; Herfarth, Klaus; Bruland, Øyvind S.; Welzel, Thomas; Haberer, Thomas; Ellerbrock, Malte; Debus, Jürgen; Uhl, Matthias; Seidensaal, Katharina (Cancers, 2022)
Radiotherapy is a crucial component in the multimodal treatment of Ewing sarcoma; it can be applied for local disease in addition to surgery or as definitive treatment for inoperable disease. Particularly in pelvic Ewing sarcoma, definitive radiotherapy offers the possibility of avoiding extensive and potentially mutilating resections and preserving crucial neurological functions. Adult patients with primary or locally recurrent pelvic Ewing sarcoma treated with curative intent with protons for primary disease and carbon ions for recurrent disease at the Heidelberg Ion-Beam Therapy Center (HIT) were considered for this retrospective analysis. We report excellent dosimetric characteristics in the treatment with protons in comparison to photon IMRT and promising early clinical outcomes. Particle therapy in adult pelvic Ewing sarcoma is shown to be feasible in a consecutive patient cohort. However, further long-term follow-up is needed to assess late toxicity and clinical outcomes.
Gesehen am 09.11.2023